Polyvinyl alcohol adhesive for hydrogen storage alloy electrode as well as preparation method and application of polyvinyl alcohol adhesive
A polyvinyl alcohol binder with a non-aqueous solvent and additives addresses electrolyte distribution and stability issues, enhancing hydrogen storage alloy electrode performance by improving structural stability and conductivity.
Patent Information
- Application Number
- CN202411364113.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-28
- Publication Date
- 2024-12-27
AI Technical Summary
Existing adhesives for hydrogen storage alloy electrodes, particularly water-based and oil-based adhesives, face issues such as poor electrolyte distribution, increased polarization, reduced discharge performance, and instability in strong alkaline solutions, leading to decreased battery capacity and cycle life.
A polyvinyl alcohol binder is prepared using a non-aqueous solvent like propylene glycol, with the addition of a cross-linking agent (maleic anhydride) and an ion conductive agent (stannous chloride) to enhance stability and conductivity, avoiding reactions with active metals and improving electrode contact.
The new binder improves structural stability, enhances electrochemical performance, and maintains discharge capacity and cycle stability by preventing reactions with active materials, resulting in improved discharge capacity and extended cycle life.
Smart Images

Figure CN119193045A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of binder preparation, and in particular relates to a polyvinyl alcohol binder for hydrogen storage alloy electrodes and a preparation method and application thereof. Background Art
[0002] At present, the commonly used adhesives for battery electrodes are water-based adhesives and oil-based adhesives. The adhesives used for hydrogen storage alloy electrodes are PVA, CMC, PTFE, silicone, conductive adhesives, etc. In practice, water-soluble adhesives such as PVA and CMC are mostly used as electrode adhesives.
[0003] Among them, oily adhesives will make the wettability of electrolyte to alloy powder inside the negative electrode worse, and make the electrolyte distribution inside the electrode uneven, reducing the surface area of the electrochemical reaction and making it difficult for the electrolyte to diffuse into the electrode, which will lead to increased polarization of the electrode during charging and discharging, and reduced high current discharge performance. In addition, oily adhesives are generally electrically insulating, and conductive agents need to be added to make them conductive. At the same time, some harmful organic solvents are not conducive to environmental protection. However, hydrophobic adhesives generally have good alkali resistance, and capacity decay caused by alloy powder falling off due to poor adhesive bonding performance will not occur during the electrode cycle.
[0004] Aqueous adhesives with water as the medium can solve many of the above problems. Generally speaking, aqueous adhesives have a small ohmic impedance and can make the electrolyte fully contact with the alloy powder inside the negative electrode, increase the effective surface area of the electrochemical reaction, reduce the nuclear polarization of the electrode internal resistance, and have better large current discharge performance of the electrode. However, aqueous adhesives have poor stability and often swell in strong alkaline solutions, which deteriorates the bonding ability. As the charge and discharge cycle proceeds, the hydrogen storage alloy powder will fall off the electrode, causing the battery capacity to decrease and the cycle life to be affected. Moreover, aqueous adhesives generally use water as the medium. In slurry-drawn or paste-coated negative electrodes, the water in the adhesive reacts with some active metals and active particles in the active material to release heat, significantly reducing the performance of the active material. Summary of the invention
[0005] In view of the above technical problems, the present invention proposes a polyvinyl alcohol binder for hydrogen storage alloy electrodes and a preparation method and application thereof. The polyvinyl alcohol binder prepared by the present invention can improve the structural stability between hydrogen storage active materials and current collectors and between active materials, promote good contact between electrodes and electrolytes, reduce the reaction between the binder and active materials, and improve its electrochemical performance. The binder can also be used in the preparation of other types of battery electrodes.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A method for preparing a polyvinyl alcohol binder for a hydrogen storage alloy electrode comprises the following steps:
[0009] Glycerol is added to the polyvinyl alcohol aqueous solution, heated and stirred, and then distilled under reduced pressure to obtain the hydrophilic binder.
[0010] Preferably, the amount of polyvinyl alcohol added to the polyvinyl alcohol adhesive is 5%-8% of the sum of the mass of polyvinyl alcohol and glycerol.
[0011] Preferably, the polyvinyl alcohol aqueous solution is obtained by adding water to polyvinyl alcohol, and then heating and stirring at 90° C. Wherein, polyvinyl alcohol (specification: PVA 17-99).
[0012] Preferably, the usage ratio of the polyvinyl alcohol to water is: (6-8) g: 50 mL.
[0013] Preferably, the preparation method further comprises:
[0014] A cross-linking agent and an ion conductive agent are added to the solution after the reduced pressure distillation, and then heated and stirred to obtain the hydrophilic binder.
[0015] Beneficial effects: The present invention modifies the polyvinyl alcohol type adhesive, selects a non-aqueous solvent to prepare a polyvinyl alcohol solution, and then adds different proportions of a cross-linking agent and an ion conductive agent. Through comparative tests, the prepared adhesive significantly improves the shortcomings of the above-mentioned polyvinyl alcohol adhesive.
[0016] Preferably, the added amount of the cross-linking agent and the ion conductive agent is 2% of the sum of the mass of polyvinyl alcohol and glycerol.
[0017] Preferably, the cross-linking agent is maleic anhydride;
[0018] The ion conductive agent is stannous chloride.
[0019] Beneficial effect: In the non-aqueous PVA adhesive (polyvinyl alcohol adhesive for hydrogen storage alloy electrode) of the present invention, the polyvinyl alcohol / glycerol adhesive has a powdering phenomenon after the electrode sheet is prepared and dried. After adding maleic anhydride, not only the powdering phenomenon can be solved, but also the cycle stability of the alloy electrode can be improved;
[0020] The addition of ionic conductive agents can improve the conductivity of the adhesive, but generally solid conductive agents such as carbon black are added in large amounts, which has a greater impact on the performance of the adhesive; while adding a small amount of stannous chloride can not only improve the conductivity of the adhesive, but also improve the discharge capacity of the hydrogen storage alloy electrode.
[0021] Preferably, the heating and stirring is carried out at a temperature of 100-120° C. and for a time of 1 hour.
[0022] The second technical solution of the present invention:
[0023] A polyvinyl alcohol adhesive is prepared by the above preparation method.
[0024] The third technical solution of the present invention:
[0025] Application of the above polyvinyl alcohol adhesive in the preparation of hydrogen storage alloy electrodes.
[0026] Preferably, the added amount of the polyvinyl alcohol binder is 25-75% of the mass of the magnesium-based hydrogen storage alloy powder.
[0027] Compared with the prior art, the present invention has the following advantages and technical effects:
[0028] Existing polyvinyl alcohol adhesives generally use water as a solvent, while the polyvinyl alcohol-type adhesive prepared by the present invention uses propylene glycol as a solvent. The specific preparation process is: first add water to polyvinyl alcohol, heat it, then select a non-aqueous solvent (propylene glycol), and remove water by reduced pressure distillation to prepare a non-aqueous polyvinyl alcohol adhesive. Then, different proportions of a cross-linking agent and an ion conductive agent can be added according to actual needs. The prepared adhesive has excellent stability and can be stably used in strong alkaline solutions. Since it does not contain water, it will not react with active metals and active particles in the electrode material to release heat, and thus will not significantly reduce the activity, thereby ensuring the discharge capacity and cycle stability of the hydrogen storage alloy electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0030] Figure 1 The discharge capacity cycle curves of the electrodes prepared by the binders of Examples 1-3 of the present invention and Comparative Example 1 are shown;
[0031] Figure 2 The graph of electrode cycle stability of the binder (b) of Example 1 of the present invention with different dosages;
[0032] Figure 3 The graph of electrode cycle stability of binders with different PVA contents;
[0033] Figure 4 The graph of electrode cycle stability of binders with different maleic anhydride contents;
[0034] Figure 5 The graph of electrode cycle stability of binders with different SnCl2 contents;
[0035] Figure 6The following are photos of the adhesives prepared in Comparative Example 2 (a) and Example 1 (b). DETAILED DESCRIPTION
[0036] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0037] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0038] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0039] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0040] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0041] The embodiment of the present invention provides a method for preparing a polyvinyl alcohol binder for a hydrogen storage alloy electrode, comprising the following steps:
[0042] Glycerol is added to the polyvinyl alcohol aqueous solution, heated and stirred, and then distilled under reduced pressure to obtain the hydrophilic binder.
[0043] In some preferred embodiments, the polyvinyl alcohol aqueous solution is obtained by adding water to polyvinyl alcohol, followed by heating and stirring at 90°C.
[0044] In some preferred embodiments, the usage ratio of polyvinyl alcohol, water and glycerol is: 6-8 g: 50 mL: 92-94 g.
[0045] The embodiment of the present invention also provides another method for preparing a polyvinyl alcohol binder for a hydrogen storage alloy electrode, comprising the following steps:
[0046] Glycerol is added to the polyvinyl alcohol aqueous solution, heated and stirred, and then distilled under reduced pressure. A crosslinking agent is added to the solution after the reduced pressure distillation, and then heated and stirred to obtain the hydrophilic binder.
[0047] In some preferred embodiments, the added amount of the cross-linking agent and the ion conductive agent is 2% of the sum of the mass of polyvinyl alcohol and glycerol.
[0048] Preferably, the cross-linking agent is maleic anhydride.
[0049] The embodiment of the present invention also provides another method for preparing a polyvinyl alcohol binder for a hydrogen storage alloy electrode, comprising the following steps:
[0050] Glycerol is added to the polyvinyl alcohol aqueous solution, heated and stirred, and then distilled under reduced pressure. A crosslinking agent and an ion conductive agent are added to the solution after the reduced pressure distillation, and then heated and stirred to obtain the hydrophilic binder.
[0051] In some preferred embodiments, the ion conductive agent is stannous chloride.
[0052] In some preferred embodiments, the heating and stirring is performed at a temperature of 100-120° C. and for a time of 1 hour.
[0053] The polyvinyl alcohol binder prepared in the embodiment of the present invention can be used to prepare hydrogen storage alloy electrodes. The added amount of the polyvinyl alcohol binder is 25-75% of the mass of the magnesium-based hydrogen storage alloy powder.
[0054] In a preferred embodiment, the added amount of the polyvinyl alcohol binder is 50% of the mass of the magnesium-based hydrogen storage alloy powder.
[0055] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0056] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.
[0057] The raw materials used in the present invention are all purchased from the market.
[0058] The technical solution of the present invention is further illustrated by the following embodiments.
[0059] Example 1
[0060] A method for preparing a polyvinyl alcohol binder for a hydrogen storage alloy electrode comprises the following steps:
[0061] Add 50 mL of water to 6 g of polyvinyl alcohol, heat to 90°C, stir to dissolve, add 94 g of propylene glycol, continue stirring for 1 hour, heat to 110°C, and distill under reduced pressure to remove water in the system to obtain a non-aqueous solvent adhesive b.
[0062] Example 2
[0063] A method for preparing a polyvinyl alcohol binder for a hydrogen storage alloy electrode comprises the following steps:
[0064] Add 50 mL of water to 6 g of polyvinyl alcohol, heat to 90°C, stir to dissolve, add 94 g of propylene glycol, continue stirring for 1 hour, heat to 110°C, remove water in the system by vacuum distillation, add 2% maleic anhydride, continue heating and stirring for 1 hour to obtain non-aqueous solvent adhesive c.
[0065] Example 3
[0066] A method for preparing a polyvinyl alcohol binder for a hydrogen storage alloy electrode comprises the following steps:
[0067] Add 50 mL of water to 6 g of polyvinyl alcohol, heat to 90°C, stir to dissolve, add 94 g of propylene glycol, continue stirring for 1 hour, heat to 110°C, remove water in the system by vacuum distillation, add 2% maleic anhydride and 2% stannous chloride, continue heating and stirring for 1 hour to obtain non-aqueous solvent adhesive d.
[0068] Comparative Example 1
[0069] A method for preparing a water-based polyvinyl alcohol adhesive comprises the following steps:
[0070] Add 94 g of water to 6 g of polyvinyl alcohol, heat to 90°C, and stir to dissolve to obtain adhesive a.
[0071] Comparative Example 2
[0072] The adhesive was prepared by direct mixing of 6 g of polyvinyl alcohol with 94 g of glycerol.
[0073] Effect verification example 1 Cyclic stability test of different types of binders
[0074] The test electrodes were prepared using the four adhesives prepared in the above Examples 1-3 (adhesives b, c, d) and Comparative Example 1 (adhesive a):
[0075] Take 1g of the above-mentioned binder and 2g of the magnesium-based hydrogen storage alloy powder (composition: Mg 2.3 Ni+1.3Ni+0.2Ti+0.1Mg, first ball-mill Mg powder and Ni powder according to the proportion to prepare Mg2.3 Ni, and then add the corresponding Ni powder, Ti powder, and Mg powder to make it by ball milling), stir evenly, apply it on a 4cm*4cm nickel foam, dry it at 120℃ for 6h, press it with a tablet press, cut it into small discs, weigh it, subtract the mass of the nickel foam, and use the data as the active material parameter. The prepared electrode is used as the test electrode (negative electrode), and the sintered NiOOH / Ni(OH)2 auxiliary electrode is used as the positive electrode. The cycle stability test is carried out using the LAND battery test system of Wuhan Landian Electronics Co., Ltd. The test conditions are as follows:
[0076] 100mAh g -1 Charge for 4 hours, let stand for 10 minutes, 50mAh g -1 Discharge to 0.9V, electrolyte is 6mol·L -1 of KOH aqueous solution.
[0077] Figure 1 The discharge capacity cycle curves of the electrodes prepared according to the binders of Examples 1-3 of the present invention and Comparative Example 1 are shown; Figure 1 It can be seen that the polyvinyl alcohol adhesive prepared by non-aqueous solvent, due to the absence of water, reduces the reaction with active metals (such as magnesium, etc.) and active particles in the hydrogen storage alloy, retains the activity of the active substance, and compared with the water-soluble polyvinyl alcohol adhesive, the discharge capacity is significantly improved, especially the initial discharge capacity, which is increased by 2-3 times.
[0078] Effect verification example 2 Effect of different binder dosage on electrode cycle stability
[0079] The magnesium-based hydrogen storage alloy material used was homemade (Mg2Ni+1.3Ni+0.2Ti), and the binder (b) was selected. Weigh 0.5g, 1g, and 1.5g of binder b and 2g of magnesium-based hydrogen storage alloy powder respectively to prepare electrodes. The electrode preparation and cycle stability test conditions are the same as those in effect verification example 1, and the same below.
[0080] Figure 2 The cyclic stability diagram of the adhesive (b) of Example 1 of the present invention with different dosages is shown in FIG. Figure 2 It can be seen that the amount of binder b is small, the initial discharge capacity is high, but the cycle stability is poor. As the amount of binder increases, the initial discharge capacity decreases, but the cycle stability is good. As the amount of binder continues to increase, the cycle stability becomes worse. Therefore, on the whole, the ratio of 1g binder to 2g alloy powder has a better effect.
[0081] Effect verification example 3 Effect of different PVA contents on electrode cycle stability
[0082] Magnesium-based hydrogen storage alloy powder (Mg 2.3Ni+1.3Ni+0.2Ti+0.1Mg) was prepared by mixing the binder and the alloy powder in a mass ratio of 1:2 to prepare the electrode. The electrode preparation and cycle stability test conditions were the same as those in effect verification example 1. The PVA content in the binder was different, specifically 2%, 4%, 5%, 6%, and 8%.
[0083] Figure 3 The electrode cycle stability diagram of the binder with different PVA content (i.e. the percentage of polyvinyl alcohol in the sum of the mass of polyvinyl alcohol and glycerol) is shown in Figure 2. Figure 3 6% is the binder prepared in Example 1, and the only difference from Example 1 is the amount of PVA and glycerol added, based on a total of 100g of PVA and glycerol added; Figure 3 2% is 2g polyvinyl alcohol and 98g propylene glycol); Figure 3 It can be seen that the electrode cycle stability of the binder with PVA content between 5% and 8% is better.
[0084] Effect verification example 4 Effect of different contents of maleic anhydride on electrode cycle stability
[0085] Based on the 6% PVA content in Effect Verification Example 3, different amounts of maleic anhydride were added, and the preparation process was referred to Example 2 to prepare the adhesive.
[0086] The magnesium-based hydrogen storage alloy powder (Mg2Ni+1.3Ni+0.2Ti) used was homemade, and the mass ratio of the binder to the alloy powder was 1:2 to prepare the electrode. The electrode preparation and cycle stability test conditions were the same as those in effect verification example 1.
[0087] Figure 4 The graph shows the electrode cycle stability of binders with different contents of maleic anhydride. It can be seen from the graph that with the increase of maleic anhydride content, the initial discharge capacity and cycle stability also gradually increase. When the maleic anhydride content is 2%, the effect is better. However, when the maleic anhydride content continues to increase, the obtained adhesive is not conducive to coating due to its excessive viscosity.
[0088] Effect verification example 5 Effect of different SnCl2 contents on electrode cycle stability
[0089] Based on the 6% PVA content in Effect Verification Example 3, different contents of SnCl2 were added, and the preparation process was referred to Example 2 to prepare the adhesive.
[0090] The magnesium-based hydrogen storage alloy material used (Mg 2.3 Ni+1.3Ni+0.2Ti+0.1Mg) was homemade, the ratio of binder to alloy powder was 1:2, and the electrode preparation and cycle stability test conditions were the same as those in effect verification example 1.
[0091] Figure 5 The graph shows the electrode cycle stability of binders with different contents of SnCl2. It can be seen from the figure that the addition of an appropriate amount of SnCl2 is beneficial to the gradual improvement of the initial discharge capacity and the cycle stability. When the SnCl2 content is 1-2%, the change is no longer obvious. When the SnCl2 content is 2%, the initial discharge capacity is higher. When the SnCl2 content is 1%, the cycle stability is better.
[0092] Figure 6 The following are photos of the adhesives prepared in Comparative Example 2 (a) and Example 1 (b). Figure 6 It can be seen that compared with Example 1, the adhesive prepared in Comparative Example 2 has more undissolved polyvinyl alcohol solids, which is not conducive to the preparation of electrode plates; while in the adhesive prepared by first adding water and then distilling off the water, the undissolved solid polyvinyl alcohol is significantly reduced, and after mixing with the active powder, it can be evenly coated.
[0093] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a polyvinyl alcohol binder for hydrogen storage alloy electrodes, characterized in that: The following steps are involved: Glycerol is added to the polyvinyl alcohol aqueous solution, heated and stirred, and then distilled under reduced pressure to obtain the hydrophilic binder.
2. The method for preparing a polyvinyl alcohol binder for hydrogen storage alloy electrode according to claim 1, characterized in that: The polyvinyl alcohol aqueous solution is obtained by adding water to polyvinyl alcohol and then heating and stirring at 90° C. The dosage ratio of the polyvinyl alcohol to water is: (5-8) g: 50 mL.
3. The method for preparing a polyvinyl alcohol binder for hydrogen storage alloy electrode according to claim 1, characterized in that: The added amount of polyvinyl alcohol in the polyvinyl alcohol adhesive is 5%-8% of the sum of the mass of polyvinyl alcohol and glycerol.
4. The method for preparing a polyvinyl alcohol binder for hydrogen storage alloy electrodes according to claim 1, characterized in that: The preparation method further comprises: A cross-linking agent and / or an ion conductive agent is added to the solution after the reduced pressure distillation, and then heated and stirred to obtain the hydrophilic binder.
5. The method for preparing a polyvinyl alcohol binder for hydrogen storage alloy electrodes according to claim 4, characterized in that: The addition amount of the cross-linking agent and the ion conductive agent is 2 wt.%.
6. The method for preparing a polyvinyl alcohol binder for hydrogen storage alloy electrode according to claim 4 or 5, characterized in that: The cross-linking agent is maleic anhydride; The ion conductive agent is stannous chloride.
7. The method for preparing a polyvinyl alcohol binder for hydrogen storage alloy electrodes according to claim 1, characterized in that: The heating and stirring is performed at a temperature of 100-120° C. and for a time of 1 hour.
8. A polyvinyl alcohol adhesive, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the polyvinyl alcohol binder as claimed in claim 8 in preparing hydrogen storage alloy electrodes.
10. Use of the polyvinyl alcohol binder according to claim 9 in preparing a hydrogen storage alloy electrode, characterized in that: The added amount of the polyvinyl alcohol adhesive is 25-75 wt.%.